2014
DOI: 10.2174/1876325101408010009
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Effects of Bisphenol A on Dopaminergic Neurons: An Experiment on Adult Rats

Abstract: Abstract:The vulnerability of developing brains to environmental chemicals has been reported. Here, we examined the temporal effects of bisphenol A on dopaminergic neurons. Exposure of 5-day-old rats to bisphenol A caused hyperactivity in juveniles, after which spontaneous motor activity leveled off at 8 weeks of age, when apoptotic cell death was still observed along with the loss of tyrosine hydroxylase immunoreactivity. Accumulation of α-synuclein, a pathological marker of neurodegeneration, was also detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In line with our findings, Pradyumna and colleagues showed that BPA treatment induced a significant upregulation of both PD-associated αSyn and leucine-rich repeated kinase 2 (LRRK2) proteins in zebrafish 38 . αSyn accumulation in neurons after BPA exposure has also been reported in mammals, being upregulated in the substantia nigra pars compacta of adult rats that were neonatally treated 39 . Moreover, when mice were exposed in utero to human-relevant doses of BPA, αSyn was one of the most upregulated genes as shown by Ingenuity Pathway Analysis 40 .…”
Section: Discussionmentioning
confidence: 63%
“…In line with our findings, Pradyumna and colleagues showed that BPA treatment induced a significant upregulation of both PD-associated αSyn and leucine-rich repeated kinase 2 (LRRK2) proteins in zebrafish 38 . αSyn accumulation in neurons after BPA exposure has also been reported in mammals, being upregulated in the substantia nigra pars compacta of adult rats that were neonatally treated 39 . Moreover, when mice were exposed in utero to human-relevant doses of BPA, αSyn was one of the most upregulated genes as shown by Ingenuity Pathway Analysis 40 .…”
Section: Discussionmentioning
confidence: 63%
“…Accordingly, Pradyumna and colleagues showed that BPA treatment induced a significant upregulation of both PDassociated αSyn and leucine-rich repeated kinase 2 (LRRK2) proteins in zebrafish [33]. αSyn accumulation in neurons after BPA exposure has also been reported in mammals, being upregulated in the substantia nigra pars compacta of adult rats that were neonatally treated [34]. Moreover, when mice were exposed in utero to human-relevant doses of BPA, αSyn was one of the most upregulated genes as shown by Ingenuity Pathway Analysis [35].…”
Section: Discussionmentioning
confidence: 95%
“…Several authors sustain that BPA exposure can be associated with neurodevelopmental disorders (autism spectrum disorder, attention de cit hyperactivity disorder) or with neurodegenerative disorders (Parkinson's Disease, amyotrophic lateral sclerosis) (Homberg, 2016;Ishido 2014;Morrice 2018). Although the mechanisms of BPA on brain development are not fully understood, numerous studies sustain that, it may impair neural stem cell proliferation and differentiation, synapse formation and synaptic plasticity, especially in the hippocampus and prefrontal cortex (Ali 2017 ;Carr 2003; Hass 2016).…”
Section: Introductionmentioning
confidence: 99%